A novel semi-coupled solid desiccant heat pump system Part 2: Experimental investigation. (January 2021) - Ge, T.S.; Yang, T.Y.; Lu, F.L.; Dai, Y.J.; Wang, R.Z.
Highlights: An experimental setup of novel solid desiccant heat pump system is established. The novel system can supply air with low temperature and COP still more than 4. Experiments show that the novel system performs better in high temperature and humidity ratio. Abstract: A novel semi-coupled solid desiccant heat pump (SCSDHP) system, in which a desiccant coated evaporator (DCE) and a conventional evaporator (CE) operate in series, is proposed to realize high COP and improve thermal comfort. In order to determine the parameters of the heat exchanger and verify the superiority of this system, the simulation model of the system has been established. In this part of study, an experimental setup is built and tested to evaluate performance of SCSDHP system. The results show that the SCSDHP system can supply satisfactory air under the typical ARI conditions. Compared with SDHP system, the supply air temperature is reduced by about 7–8 °C, and the corresponding cooling power is increased by more than 50%. It is noteworthy that the COP of this novel SCSDHP system is still more than 4 which is higher than the traditional vapor compression system. The results also show that this novel system can be applied in a wide range of temperature and humidity, the COP will be higher when applied in higher temperature and humidity ratio.